The prevention of spinal pain - a systematic review - Kałużna, Anna; Kałużny, Krystian; Wołowiec, Łukasz; Płoszaj, Ola; Zukow, Walery; Kochański, Bartosz; Hagner, Wojciech (Journal of Education, Health and Sport, 2017)
The spinal pain is a big social problem and a challenge for modern medicine. The basis of therapeutic activities is prevention, which is very important in stopping the progress of this disease. The task of prevention is patient education, which is intended to increase patient awareness about the pathogenetic mechanism of the problem of spinal pain and the consequences of lack of knowledge about the health-promoting behaviors related to this problem.